Coup d'États, institutional change, and productivity - Daniel L. Bennett; Christian Bjørnskov; Stephen F. Gohmann (Research Institute of Industrial Economics (IFN), 2025)
Understanding the consequences and recovery for countries hit by adverse national events such as political crises is central to understanding long-run development dynamics. Utilizing the Coleman boat framework, we develop a micro-foundation based theoretical framework grounded in public choice theory and institutional economic theory to theorize about the productivity consequences of political coups. Our theory suggests two consequences. First, coups create regime uncertainty that distorts the judgment of entrepreneurs and firm managers, resulting in their delaying or abandoning altogether investment in potential productivity-enhancing innovation projects. Second, in addition to regime uncertainty, institutional changes in the aftermath of a coup exert long-run impacts on national productivity by creating a misalignment of the formal institutional environment. Our model allows us to disentangle the productivity effects of institutional uncertainty from actual institutional change following a political crisis. We assemble a unique longitudinal dataset consisting of 39 nations covering the period 1950-2012 to empirically test our hypotheses using panel data methods. We further explore some of the boundary conditions of our analysis.
Keywords: E02; O31; O43; P47; 330; Coups; regime change; institutional change; productivity